2012
DOI: 10.1111/j.1757-1707.2012.01208.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of culturable bacterial endophytes of switchgrass (Panicum virgatum L.) and their capacity to influence plant growth

Abstract: Switchgrass (Panicum virgatum L.) is a perennial warm season grass that is native to the plains of North America and is widely grown as a forage, bioenergy or groundcover crop. Despite its importance, a bottleneck in switchgrass production is poor seedling vigor, which as a perennial crop represents an important time for management. Herein, data identify a suite of culturable bacterial microflora extracted from switchgrass, and show their capability to influence host plant growth and development. A total of 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 42 publications
0
43
0
Order By: Relevance
“…The Proteobacteria, for example, have diazotrophic bacterial members and could help to explain their greater relative abundance and greater nitrogen fixation potential in Alamo relative to Dacotah. Similarly, the positive association of bacilli with many other taxa within the bacterial network, and its greater abundance in the cultivable community in Alamo compared with Dacotah is consistent with a growth supportive role played by these bacteria (Lopez-Bucio et al, 2007;Nautiyal et al, 2013;Xia et al, 2013;Gagne-Bourque et al, 2015). Presumably, the surrounding taxa that benefit would in return provide resources that support the growth of the bacilli.…”
Section: Plant-microbial Amino Acids In the Root-zonementioning
confidence: 58%
See 1 more Smart Citation
“…The Proteobacteria, for example, have diazotrophic bacterial members and could help to explain their greater relative abundance and greater nitrogen fixation potential in Alamo relative to Dacotah. Similarly, the positive association of bacilli with many other taxa within the bacterial network, and its greater abundance in the cultivable community in Alamo compared with Dacotah is consistent with a growth supportive role played by these bacteria (Lopez-Bucio et al, 2007;Nautiyal et al, 2013;Xia et al, 2013;Gagne-Bourque et al, 2015). Presumably, the surrounding taxa that benefit would in return provide resources that support the growth of the bacilli.…”
Section: Plant-microbial Amino Acids In the Root-zonementioning
confidence: 58%
“…A recent study, for example, identified diverse sets of nitrogen-fixing bacteria associated with roots and shoots of switchgrass (Bahulikar et al, 2014). Other studies focused on targeted approaches of using nitrogen-fixing bacterial endophytes to improve productivity across cultivars (Ker et al, 2012;Xia et al, 2013;Lowman et al, 2016). Plant bacterial associations and how they differ among plant species and cultivars can help to understand the interplay of traits important for defining the drivers of a globally significant plant-bacterial function like that of ANF.…”
Section: Introductionmentioning
confidence: 99%
“…Gammaproteobacteria have been reported as commonly dominant endophyte in plants [32]. On the other hand, [32], whereas, they have been dominantly detected in several crops as canola [33], banana [34], switch grass [35] and tobacco [36]. The determining factors of Bacilli are still unclear and needs to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…According to Robinson et al [17], soil nutrient availability can affect the wheat endophytic bacterial community through the plant growth response. Xia et al [64] showed that soil pH plays a role in endophyte community diversity in switchgrass. In the current study, endophytic bacterial community structure was significantly correlated with soil AN, AP, AK, and C/N.…”
Section: Discussionmentioning
confidence: 99%